2007
DOI: 10.2500/ajr.2007.21.2993
|View full text |Cite
|
Sign up to set email alerts
|

Choanal Polyps: An Evaluation of 53 Cases

Abstract: Endoscopic approach for complete removal of the CPs is an extremely safe and effective procedure. It should be focused on the detection of the exact origin and the extent of the polyp to prevent recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
37
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 15 publications
0
37
0
1
Order By: Relevance
“…Patients tend to have a longer duration of symptoms with ACPs than with SNIPs [63]. While the vast majority of ACPs are unilateral, synchronous bilateral involvement may be observed, along with bilateral maxillary sinusitis [61]. It is not uncommon to have concurrent SNIPs, allergic rhinitis, chronic rhinosinusitis and/or turbinate hypertrophy.…”
Section: Clinical Featuresmentioning
confidence: 99%
See 2 more Smart Citations
“…Patients tend to have a longer duration of symptoms with ACPs than with SNIPs [63]. While the vast majority of ACPs are unilateral, synchronous bilateral involvement may be observed, along with bilateral maxillary sinusitis [61]. It is not uncommon to have concurrent SNIPs, allergic rhinitis, chronic rhinosinusitis and/or turbinate hypertrophy.…”
Section: Clinical Featuresmentioning
confidence: 99%
“…The stalk of attachment within the medial wall is not usually identified by imaging, but a large, pedunculated polyp will expand into and fill the nasal cavity and/or pharynx [55,62,64,65]. Uncommonly, choanal polyps will arise from the sphenoid or ethmoid sinus, referred to as sphenochoanal or ethmochoanal polyps, revealing a stalk of attachment in the named sinus [61]. Conservative combination endoscopic (Functional Endoscopic Sinus Surgery: FESS) and open surgery (miniCaldwell procedure) to include the stalk and sinus contents, seems to yield the lowest risk of recurrence [55,60,64], especially if the point of attachment cannot be identified.…”
Section: Clinical Featuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Concerning the association of ACP with OSA only three documented cases have been published so far [5,14,16]. Many authors list obstructive sleep disorders (loud snoring, sleep apnoea) as possible manifestations of ACPs [23,30,[33][34][35]. But in none of those studies the evaluation of diagnosis becomes evident and the distinction between loud snoring and full blown OSA has not been elaborated.…”
Section: Discussionmentioning
confidence: 93%
“…The common site is posterior wall followed by inferior and lateral walls. It should be focused on the detection of the exact origin and the extent of the polyp to prevent recurrence [16,18]. Bozzo et al [19] observed two recurrences, both in pediatric cases who evidently underwent an incomplete surgical removal of antral mucosa at its inferior aspect, probably due to the fear of damaging the teeth buds.…”
Section: Discussionmentioning
confidence: 98%